Examine how cultural beliefs and practices influence adolescents' knowledge of HIV/AIDS and their willingness to seek testing and treatment - Purwanto, Edi; Ardianzyah, Muhamad Viki Nur (Science Midwifery, 2025)
HIV/AIDS remains a major health challenge among adolescents. Cultural beliefs and religious practices are believed to influence adolescents’ knowledge and their willingness to undergo testing and treatment. This study aims to examine the influence of cultural and religious beliefs on adolescents’ knowledge of HIV/AIDS and their willingness to seek testing and treatment. A cross-sectional quantitative approach was used involving 30 adolescents with structured questionnaires. Data were analyzed using chi-square tests and binary logistic regression in SPSS. The results showed no significant association between HIV knowledge and willingness to test (p=0.753). However, negative attitudes toward PLWHA significantly reduced the willingness to undergo testing (p=0.045), and religious influence showed a near-significant tendency toward affecting testing behavior (p≈0.064). It is concluded that attitudes toward PLWHA and religious values exert a greater influence than knowledge alone. Therefore, culturally and religiously sensitive interventions are needed to improve HIV testing awareness among adolescents.